SISTEM PEMELIHARAAN ANJING SEBAGAI SALAH SATU HEWAN PENULAR RABIES PADA PENDERITA RABIES DI PROVINSI BALI TAHUN 2011 - pasek kardiwinata; Made Sutarga; made subrata; Putu Suariyani (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2012)
The number of cases of dog bites in the province of Bali has been a rise high enough. 2009, thenumber of dog bites 21 806 bite, the amount of gain VAR as many as 18 825 people, as many as27 people died. October 16, 2010 the number of bites as much as 44 629 bites, which get the VARas many as 38 982 people, as many as 62 people died. According Disnak (2010) maintance systemof dog conducted by the Balinese tend to be untied so the dogs are freely to enter and out of thehouse. An objective to be achieved in this study was to determine the system of dog maintancewhich is one of the animals transmi! ing rabies (HPR) in patients with rabies in Bali.The study design used was descriptive cross-sectional. The population in this study were all patients who die from the bite of HPR in Bali in 2010-2011, the sample was part of the patientpopulation rabies recorded in Bali Provincial Health O? ce in 2010-2011 with a porpusivesampling techniquePeople with rabies who had HPR were 35.4%, HPR which were not given VAR about 63.6%, andmostly were detachable cages. The reason of had dogs were to guard the house and hobbyists.Dogs that bite the sample were not known who were the owner / wild, so a er the bite were notknown its existence, it is di? cult to observe, there were also death but were killed only a smallpart due to illnessIt showed that the mantaince system of dog were not good. The results of this study can be usedas a reference to the stakeholders in order to prevent disease, especially rabies in dogs and themaintenance system. Future studies on rabies vaccination coverage in dogs and the preventionmodel in order to reduce the incidence of rabies in the Bali.